Does the interruption of eye contact between humans and Caribbean reef sharks, Carcharhinus perezi, influence the sharks' approach patterns?. Issue 3 (3rd July 2021) - Ritter, Erich K.; Amin, Raid
ABSTRACT: As ecotourists become increasingly interested in snorkeling and diving with sharks, it is important to establish directives for safe interactions. The study considered eye contact between humans and approaching sharks, examining specifically whether an interruption in it owing to, for example, a person glancing at a camera or regarding where to retreat, would affect a shark's behavior. In standardized field tests, divers maintained or interrupted eye contact with approaching Caribbean reef sharks, Carcharhinus perezi. The results showed a significant difference in the sharks' approaches depending on whether the divers maintained or interrupted eye contact with them. More specifically, the analysis revealed that sharks came significantly closer to the divers when eye contact was interrupted and also reduced their speed.